The German Radiological Society and the Protagonists of Radiology during the Time of National Socialism – State of Research, Explanation Attempts, Desiderata and Research Prospects - Schmidt, M.; Winzen, T.; Groß, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
The intention of the authors is the recognition and critical analysis of efforts to study the history of the German Radiological Society during the time of National Socialism from 1933 to 1945 with the goal of determining existing desiderata and identifying the resulting research prospects. There is a need to study concrete individual biographies of radiologists (members of the German Radiological Society, perpetrators, and victims) and their careers before and after 1945 as well as the importance of the interdisciplinarity of the discipline and the lack of institutional involvement during the “Third Reich”. Moreover, the comparatively difficult starting situation of the study of the history of the German Radiological Society is discussed.Key Points:• In the history of the German Radiological Society in the era of National Socialism there exist research desiderata.• The research of the history of the society faces a number of problems that are addressed.• The history of the German Radiological Society will provide an interesting insight into a comparatively young and interdisciplinary field.Citation Format:• Schmidt M, Winzen T, Groß D. The German Radiological Society and the Protagonists of Radiology during the Time of National Socialism – State of Research, Explanation Attempts, Desiderata and Research Prospects. Fortschr Röntgenstr 2015; 187: 425 – 429
Keywords: health policy and practice; history; national socialism; german radiological society; structural developments of radiological discipline